Triptycene-supported bimetallic salen porous organic polymers for high efficiency CO2 fixation to cyclic carbonates. Issue 11 (27th April 2021) - Zheng, Yingting; Wang, Xiqian; Liu, Chao; Yu, Baoqiu; Li, Wenliang; Wang, Hailong; Sun, Tingting; Jiang, Jianzhuang
Abstract : Triptycene units in bimetallic salen POPs are envisaged to support the alignment of bimetallic salen macrocycles in side walls of channels for exposing more metal active sites resulting in the high efficiency coupling reaction of epoxides with CO2 . Abstract : Exposing the active sites of heterogeneous catalysts is very important for catalysis. Herein, a series of two-dimensional (2D) bimetallic salen-based porous organic polymers BSPOPs (BSPOP-Al, BSPOP-Co, and BSPOP-Ni) have been elaborated by the reaction of 2, 3, 6, 7, 14, 15-hexaammoniumtriptycene with 2, 6-diformyl-4-methylphenol in the presence of metal salts, namely, aluminum chloride, cobalt acetate, and nickel acetate, respectively. Different from 2D π–π packing porous organic polymers, triptycene units are envisaged to support the alignment of bimetallic salen macrocycles in the side walls of channels for exposing many more catalytic metal sites. The bimetallic salen structure has been confirmed by inductively coupled plasma optical emission spectrometry (ICP-OES), infrared (IR) spectrometry, and nuclear magnetic resonance (NMR) studies. The porous nature of these metal-containing organic polymers has been disclosed by gas sorption experiments. The isosteric heat of CO2 adsorption ( Q st ) for this series of organic polymers is as high as 42.1 kJ mol −1 for cobalt species, indicating their high affinity towards carbon dioxide. The synergistic effects from their porous nature together with high affinities between CO2 and Lewis acidic metal ions, as well as the many active catalytic sites in the channels, result in the high efficiency coupling reaction of epoxides with CO2 upon BSPOP-Co. The present work not only provides a new porous organic polymer but also proposes an effective strategy to expose many more active sites for heterogeneous catalysis.